Generating Dutiful Members in Communities of 'Rational Choice' - Holger Ziegler (Social Work & Society, 2003)
The study 'Youth Welfare as Prevention - The reconfiguration of support and control in advanced liberalism' is part of the Graduate program 'Youth Welfare in Transition' funded by the 'German Research Association'. In empirical terms it is based on both interviews with professionals, reconstructive discourse analysis based on documents and programs as well as a secondary analysis of a range of existing studies.